Hedging in airline risk management - Mäntynen, Tuure (My University, 2026)
The purpose of this thesis is to investigate how airlines manage their risks from financial per spective as well as from operational perspective. The airline industry is exposed to fuel price fluctuations and volatility, which affects financial stability and operating costs. The performance and different hedging strategies with derivatives have been discussed a lot in the literature. Furthermore, the purpose is also studying effectiveness of different strategies using derivatives as hedging. Thesis investigates hypothesis concerning the use of derivatives and how they affect earnings and cash-flows volatility and do they improve financial stability. The analysis examines the ef fectiveness of hedging and does hedging varies between airlines. Geopolitical circumstances are always big question in the industry and thesis also investigates how companies try to minimize operative risks. Hedging jet fuel can lower earnings and cash flow volatility even though companies’ values are variable and depend on context. Conclusions show that hedging effectiveness makes a differ ence in the choice of instruments and in market conditions. This leads airlines versatility in pro tecting themselves from an operational as well as financial perspective. Literature often sees larger airlines on average more efficient in the use of derivatives and in risk management. This is explained through better resources and economies of scale but smaller airlines hedging strategies can have a positive effect especially when hedging is executed sys tematically and considering the airline’s risk profile.

Tämän opinnäytetyön tarkoituksena on tutkia, miten lentoyhtiöt hallitsevat riskejään sekä taloudellisesta että operatiivisesta näkökulmasta. Lentoala on alttiina polttoaineen hinnanvaihteluille ja volatiliteetille, mikä vaikuttaa taloudelliseen vakauteen ja käyttökustannuksiin. Johdannaisten suorituskykyä ja erilaisia ​​suojausstrategioita on käsitelty paljon kirjallisuudessa. Lisäksi tarkoituksena on tutkia eri strategioiden tehokkuutta johdannaisten käytössä suojauksena. Opinnäytetyössä tutkitaan hypoteeseja johdannaisten käytöstä ja siitä, miten ne vaikuttavat tulokseen ja kassavirtoihin sekä parantavatko ne taloudellista vakautta. Analyysissä tarkastellaan suojauksen tehokkuutta ja sitä, vaihteleeko suojaus lentoyhtiöiden välillä. Geopoliittiset olosuhteet ovat aina suuri kysymys alalla, ja opinnäytetyössä tarkastellaan myös sitä, miten yritykset pyrkivät minimoimaan operatiivisia riskejä. Lentopolttoaineen suojaus voi alentaa tulojen ja kassavirran volatiliteettia, vaikka yritysten arvot vaihtelevat ja riippuvat kontekstista. Johtopäätökset osoittavat, että suojauksen tehokkuus vaikuttaa instrumenttien valintaan ja markkinaolosuhteisiin. Tämä johtaa lentoyhtiöiden monipuolisuuteen suojautua sekä operatiivisesta että taloudellisesta näkökulmasta. Kirjallisuudessa suuret lentoyhtiöt nähdään usein keskimäärin tehokkaampina johdannaisten käytössä ja riskienhallinnassa. Tämä selittyy paremmilla resursseilla ja mittakaavaeduilla, mutta pienempien lentoyhtiöiden suojausstrategioilla voi olla positiivinen vaikutus erityisesti silloin, kun suojausta toteutetaan systemaattisesti ja ottaen huomioon lentoyhtiön riskiprofiili.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Kauppatieteiden kandidaattiohjelma|en=Bachelor Programme in Business Studies|